Participation and Exegesis: Response to Catherine Pickstock - Levering, Matthew (Modern theology, 2005)
This essay pursues Catherine Pickstock’s "metaphysical-epistemological" insights but in a "metaphysical-hermeneutical" direction. In particular, Pickstock’s case for a fourteenth-century break from the metaphysics/epistemology of "participated-in perfections" receives further plausibility by looking at the movement away from patristic-medieval biblical interpretation. Drawing upon the work of Matthew L. Lamb in particular, the essay argues that nominalist metaphysical rejection of participation led to time and history being understood no longer primarily as a participatory and teleological conversatio Dei but instead now as a strictly linear (autonomous) continuum of distinct moments. "History" thus understood proved difficult to square with patristic-medieval biblical interpretation, which gradually became unintelligible to many as a "mystical" zone cut off from the "conceptual" realm of facts. As an example of the resources available in such patristic-medieval biblical interpretation, the essay treats Aquinas’s exegesis of John 3:27-36.